Exploring Interactive Furniture with EmotoCouch - Mennicken, Sarah; Brush, A.J.; Roseway, Asta; Scott, James (Adjunct Proceedings of ACM UbiComp 2014 (videos track), 2014)
People respond emotionally to other people, animals, or even objects like furniture. While current furniture is static in appearance, embedded electronics can enable furniture to change its appearance. A couch could show excitement during a party or anger when a pet scratches it. But would emotional furniture delight or annoy people? To explore the potential for emotional furniture, we built EmotoCouch. Through colored light, visual patterns, and haptic feedback, EmotoCouch expresses six emotional states: Excited, Happy, Calm, Depressed/Sad, Afraid, and Angry. This video describes the construction of EmotoCouch, feedback gathered through surveys and user interviews, and shows example EmotoCouch usage situations.